NIGARI (DEEP SEAWATER CONCENTRATE) ENHANCES THE TREADMILL EXERCISE PERFORMANCE OF GERBILS - Wang, M.-L.; Chen, Y.-J.; Cheng, F.-C. (Biology of Sport, 2014)
The beneficial effect of magnesium supplementation on exercise performance has been reported by many researchers. In the present study, the effect of nigari, a concentrate of deep seawater containing high magnesium levels, on exercise performance, was examined. Gerbils were given double-distilled water or nigari (18 mg · kg-1, po) orally 30 min before exercise. All animals were subjected to forced exercise on a treadmill for 90 min at three successive speeds of 10, 15, and 20 m · min-1. The retention numbers were recorded. The retention numbers were 85.0 ± 21.0, 46.0 ± 9.7, and 48.0 ± 14.2 in the control group, and 44.0 ± 10.9, 23.0 ± 8.4, and 13.0 ± 4.8 in the nigari-treated group at the three speeds, respectively. The retention numbers were significantly reduced at higher speeds (by 50% at 15 and 73% at 20 m · min-1, respectively) in the nigari-treated group when compared to those of the control group, respectively. Thus, nigari administration appeared to reduce retention numbers and enhance exercise performance in gerbils.